2007
DOI: 10.1007/s00408-007-9018-x
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Heat Stress Protein 70 Induction and Decreased Pulmonary Fibrosis in an Animal Model of Acute Lung Injury

Abstract: The hyperthermia-induced activation of the stress protein response allows cells to withstand metabolic insults that would otherwise be lethal. This phenomenon is referred to as thermotolerance. Heat shock protein 70 (HSP70) has been shown to play an important role in this hyperthermia-related cell protection. HSP70 confers protection against cellular and tissue injury. Our objective was to determine the effect of heat stress on the histopathology of pulmonary fibrosis caused by the administration of lipopolysa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 32 publications
2
27
0
Order By: Relevance
“…In support of this notion, Weiss and colleagues demonstrated that overexpression of Hsp70 in pulmonary epithelium reduces mortality and lung injury in a model of cecal ligation and puncture (55). Hsp70 induction was also associated with decreased pulmonary fibrosis (56), whereas ablation of the heat shock factor-1, which regulates HSP family members expression, increases susceptibility to hyperoxia in experimental models of ALI in mice (57). DnaJ (Hsp40) family proteins, Dnaja1 and Dnajb1, which are down-regulated by MV in the absence of Nrf2, by acting as co-chaperones modulate Hsp70 activity (58).…”
Section: Discussionmentioning
confidence: 90%
“…In support of this notion, Weiss and colleagues demonstrated that overexpression of Hsp70 in pulmonary epithelium reduces mortality and lung injury in a model of cecal ligation and puncture (55). Hsp70 induction was also associated with decreased pulmonary fibrosis (56), whereas ablation of the heat shock factor-1, which regulates HSP family members expression, increases susceptibility to hyperoxia in experimental models of ALI in mice (57). DnaJ (Hsp40) family proteins, Dnaja1 and Dnajb1, which are down-regulated by MV in the absence of Nrf2, by acting as co-chaperones modulate Hsp70 activity (58).…”
Section: Discussionmentioning
confidence: 90%
“…These Hsps are believed to exert a protective effect for some tissues against stresses such as exposure to high temperature, ischemia/reperfusion, and cytotoxic substances (Kawana et al 2000;Eichler et al 2005;Hagiwara et al 2007). Hsps help to maintain the metabolic and structural Fig.…”
Section: Discussionmentioning
confidence: 98%
“…These Hsps help to maintain the metabolic and structural integrity of the cells and exert protective function for some tissues against some stressors such as heat stress, ischaemia and cytotoxicity (Eichler et al 2005;Hagiwara et al 2007). The heat shock proteins (Hsp-90 alpha, 90 beta and 60) mRNA expression revealed significant variation in heart, liver and spleens of N and HE groups in PB-2 chicken which were lower in HE birds indicating the possible impact of thermal adaptation except in liver (Table 2).…”
Section: Discussionmentioning
confidence: 99%